HUBUNGAN LINGKAR PINGGANG, RASIO LINGKAR PINGGANG TERHADAP TINGGI BADAN DAN INDEKS MASSA TUBUH DENGAN KADAR ASAM URAT WANITA USIA 45-55 TAHUN - Rizki, Mawarni Uli; Probosari, Enny; Nissa, Choirun (Journal of Nutrition College, 2017)
Background: HiperuricemiaÂ  is a risk factor of degenerative diseases and metabolic syndrome. Elevated levels of uric acid are known to be linked with central obesity. Obesity can be determined by anthropometric measurements such as waist circumference, waist-to-height ratio and Body mass index. This study aimed to determine the correlation of waist circumference, waist-to-height ratio and body mass index with uric acid levels in women aged 45-55 years old. Method: This was an observational study with the cross-sectional design. Forty-six subjects were selected using simple random sampling. The measured anthropometric indices were height, weight and waist circumference. Colorimetry method was used to measure blood uric acid levels. Data were analyzed by Fisher exact and Multiple Logistic Regression test.Â  Result: A total of 19.6% (n=9) subjects had high uric acid levels. These subjects had waist circumferences of over 88 cm (37.5%), waist-to-height ratios that exceed 0.58 (31.6%) and body mass index >25,0 (25%).. There was a significant correlation between waist circumference with uric acid levels, with a prevalence ratio of 5.4 (CI 95% 1.13;25.8). On the contrary, there was no correlation between waist-to-height ratio and body mass index with uric acid levels. Conclusion: There was a significant correlation between waist circumference with uric acid levels. However, no correlation was found between waist to height ratio and body mass index with uric acid levels.